2021
DOI: 10.1038/s41559-021-01548-3
|View full text |Cite
|
Sign up to set email alerts
|

Global hunter-gatherer population densities constrained by influence of seasonality on diet composition

Abstract: The dependence of hunter-gatherers on local net primary production (NPP) to provide food played a major role in shaping long-term human population dynamics. Observations of contemporary hunter-gatherers have shown an overall correlation between population density and annual NPP, but with a thousand-fold variation in population density per unit NPP that remains unexplained. Here we build a process-based hunter-gatherer population model embedded within a global terrestrial biosphere model, which explicitly addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…This is a reminiscent demographic dynamic to the fission–fusion social organization of wild orangutans and that of ancient humans in the African continent 99 . Indeed, ecological changes towards drier habitats brought about by palaeo-climate change in the African continent 100 , 101 were unlikely to have sustained densely populated communities in the wake of human evolution 102 . Results agree, thus, with computational models, statistical analyses and phylogenetic reconstructions showing that ‘social intelligence’ was not an evolutionary driver for human (brain) evolution as much as once believed 103 105 .…”
Section: Resultsmentioning
confidence: 99%
“…This is a reminiscent demographic dynamic to the fission–fusion social organization of wild orangutans and that of ancient humans in the African continent 99 . Indeed, ecological changes towards drier habitats brought about by palaeo-climate change in the African continent 100 , 101 were unlikely to have sustained densely populated communities in the wake of human evolution 102 . Results agree, thus, with computational models, statistical analyses and phylogenetic reconstructions showing that ‘social intelligence’ was not an evolutionary driver for human (brain) evolution as much as once believed 103 105 .…”
Section: Resultsmentioning
confidence: 99%
“…Most seasonal temperature and precipitation variables showed some of the lowest explained deviances (Table 1), indicating that seasonal climatology most likely did not impose a direct limit on past forager populations densities in Late Pleistocene/Early Holocene Europe (contra 18 ). Topographic complexity, a variable shown to influence population density in other studies 11 , showed only above-average predictive accuracy (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Each environment offered particular opportunities but also posed particular challenges. While several earlier studies have pointed at temperature or seasonality as key drivers of forager demography at global or continental scales 17,18 , the specific factors that would have capped or even depressed population size are likely to have varied in both space and time. Only in understanding these limiting factors can we begin to conduct targeted investigations of how specific forager populations may have overcome them via either population-specific genetic adaptations or the sort of 'extra-somatic adaptions' 19 that are so characteristic of human culture.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is less than one spotted hyena, a carnivore whose average body mass (58.6 kg) is approximately equal to that of humans, for every 10,000 kg of prey (a ratio of predator to prey mass that holds across the Carnivora, Carbone & Gittleman, 2002). Similarly, in ethnographically known hunter-gatherers, as the proportion of meat in the diet increases, population density decreases (Zhu et al, 2021). Indeed, genetic evidence suggests a substantially smaller effective population size for ancestral humans relative to other great apes (Prado-Martinez et al, 2013), which, combined with a larger range size, also suggests lower population density.…”
Section: Range Size Population Density and Pathogen Pressurementioning
confidence: 99%
“…Pathogen pressure, in turn, could limit population density. In high productivity environments (e.g., tropics, subtropics), the population density of ethnographically known hunter-gatherers is strongly negatively associated with pathogen stress (Tallavaara et al, 2018; but see critique in Zhu et al, 2021).…”
Section: Range Size Population Density and Pathogen Pressurementioning
confidence: 99%